Critical success factors of risk‐based inspection. Issue 1 (25th April 2018) - Mohamed, Ramuna; Che Hassan, Che Rosmani; Hamid, Mahar Diana
Abstract : Risk‐based inspection (RBI) is a tool which helps ensure safe and economically viable operation. To benefit from an RBI system, the factors that affect its implementation need to be studied. This research focuses on identifying and ranking the critical success factors (CSFs) of RBI. Based on the literature review of RBI, an initial list of 28 potential CSFs was identified and complied. These CSFs were then grouped into eight factor headings according to RBI/RBM, RBIM and risk assessment process. A survey was conducted to assess and prioritizes the degree of influence of those success factors on RBI systems, while determining whether these CSFs do indeed play a critical role in the successful implementation of RBI systems as perceived by the respondents. Samples were collected to confirm the identified CSFs. The findings show that the most influential factor is "Data Collection, " and while "RBI Estimation" is the most critical factor heading in the implementation of RBI. Additionally, the findings also show that all CSFs identified are critical and relevant for Malaysian industries. © 2018 American Institute of Chemical Engineers Process Process Saf Prog 38: 4–20, 2019